The Influence of Socio-Economic and Psychological Factors on Millennial Generation’s Stock Investment Decisions - Ni Made Dwi Ratnadi (Accounting Analysis Journal, 2023)
Purpose : Increasing investment awareness among the public, especially among millen- nials, is crucial for the development of the stock market and overall financial growth. As a significant potential force, millennials can play a vital role in increasing stock investment decisions and fostering economic progress. This study aims to develop an integrated model of the influence of socioeconomic and psychological factors, namely return expectations, self-efficacy, and risk perception, on millennial stock investment decision-making behavior. Method : The research population was millennial stock investors. Non-probability sampling technique was used to obtain 336 respondents. Data were collected through the survey method using a questionnaire. Data were analyzed using the partial least square (PLS) technique. Findings : Based on the analysis, socioeconomic factors influence investment deci- sions, return expectations, self-efficacy, and risk perception. Socioeconomic factors influence investment decisions through return expectations, self-efficacy, and risk per- ception. However, risk perception does not directly affect millennial stock investment decisions. The results of this study can be used as a reference to motivate young people to invest intelligently in the stock market. Novelty : The research was conducted on the millennial generation, who have an im- portant role in stock investment decisions, considering that the millennial generation is the generation that has an important role in increasing stock investment. Keywords : Expected Return; Self Efficacy; Risk Perception; Investment Decision